Pengaruh Konsumsi Rumah Tangga, Investasi Dalam Negeri dan Pengeluaran Pemerintah Terhadap Produk Domestik Bruto di Indonesia Tahun 2014-2023 - Sekar Dwi Rachmadhani; Alin Dwi Putri; Syifa Shandy Erlia; Misfi Laili Rohmi (Jurnal Pajak dan Analisis Ekonomi Syariah, 2024)
This study aims to balance the global influence of domestic consumption, investment (PMDN), and government expenditure on Indonesia's Gross Domestic Product (GDP). This research is a digital research study that proceeds from qualitative methods using secondary digital analysis. The main focus of this research refers to the historical evolution of Indonesia's GDP from 2014 to 2023, using a multi-gallon linear regression approach. The results of the F test show that simultaneously, the influence of domestic consumption, investment (PMDN), and government expenditure has a significant influence on Indonesia's GDP. As a matter of fact, government spending has a significant influence on GDP. This analysis encourages greater attention to aspects of household expenditure and domestic investment to increase GDP value, as well as disrupting the balance of government spending. This step has been prevented and will help in the government's future planning in making policies to increase GDP.